Pengaruh Word Of Mouth, Customer Experience, Dan Kualitas Layanan Terhadap Keputusan Penggunaan Jasa PT. Pos Indonesia (Persero) Kota Probolinggo - Widiyantari, Ela; Elmas, Muhammad Syarif Hidayatullah; Yatiningrum, Agung (Universitas Panca Marga, 2024)
This study was conducted with the aim of knowing whether there is a positive and significant effect of Word Of Mouth on the Decision to Use Services of PT Pos Indonesia (Persero) Probolinggo City, knowing whether there is a positive and significant effect of Customer Experience on the Decision to Use Services of PT Pos Indonesia (Persero) Probolinggo City, knowing whether there is a positive and significant effect of Service Quality on the Decision to Use Services of PT Pos Indonesia (Persero) Probolinggo City. The type of research used in this study is quantitative research with a Causal Associative approach with Word Of Mouth, Customer Experience, and Service Quality as independent variables and Service Usage Decisions as the dependent variable. The population in this study were service users at PT Pos Indonesia (Persero) Probolinggo City with a sample of 90 respondents and the sampling technique used Based on the results of hypothesis testing, it shows that Word Of Mouth, Customer Experience, and Service Quality have a positive and significant effect on the Decision to Use Services of PT. Pos Indonesia (Persero) Probolinggo City. Keywords: Word Of Mouth, Customer Experienece, Service Quality, Service Usage Decision